Temperature influences postdispersal predation of weed seeds. Issue 1 (28th January 2016) - Noroozi, Shahrzad; Alizadeh, Hasan; Mashhadi, Hamid Rahimian
Abstract : Temperature is a key factor for the living organisms on earth. It influences weed management practices, either directly or indirectly. Field experiments were conducted to determine the effect of temperature on the postdispersal seed predation of four important weed species ( Cuscuta compestris, Stellaria media, Taraxacum officinale and Veronica persica ) in two lucerne fields in Mashhad and Chenaran, north‐eastern Iran. These two cities have the same climate: temperate and cold alpine but the temperature varies between them. Wire mesh cages were used to determine the relative importance of birds in predation and pitfall traps were used to detect the species and the activity density of invertebrate predators. The results showed that the predation preference of different weed species was significantly different between and within fields. Seed predation fluctuated widely throughout the sampling periods, matching the periodic forage harvest and regrowth cycle of lucerne. Despite the level of seed predation fluctuating, it declined toward the last sampling periods. Using wire mesh exclusion cages showed no significant effect of birds on weed seed predation in both fields. Ants, crickets and carabid beetles were the invertebrate seed predators that were caught in the pitfall traps. There were significant correlations between the mean temperature and predator activity densities and also between the predated seeds and the mean air temperature in both locations. The results of this study indicate the significant effect of temperature on postdispersal weed seed predation. Therefore, with respect to climate change and increasing global warming, it would be possible to focus on postdispersal seed predation in weed management in the future.